Orthostatic hypotension: a hidden player in the life of the frail elderly - Ormachea, Mario; Gómez Borrás, Libertad; Alfie, José (Revista del Hospital Italiano de Buenos Aires, 2011)
We investigated the presence of orthostatic hypotension (OH) and its relationship with demographic, functional, cognitive, previous medical history and active conditions, medications, hospitalizations in the last year and death during follow-up to six months in 69 elderly residents in Geriatrics of Hospital Italiano de Buenos Aires, at San Justo. OH was defined as reduction of ≥ 20 mmHg of systolic and ≥ 10 mmHg of diastolic arterial blood pressure (BP) measured between 1 and 3 minutes of postural change. OH affected 40% of the population. BP (systolic/diastolic) decreased -26/-7 and -34/-13 mmHg when sitting and standing, respectively, in the group with OH, while it decreased only 3/-1 and -3/-1 mmHg, respectively, in the group without OH. The chronotropic response was not different between groups. We found no statistically significant association between OH and Parkinson’s disease, dementia, depression, diabetes, history of falls, hip fracture, prostration, use of wheelchair, swallowing disorder, urinary incontinence, or the medication used. During follow-up 6 patients died, of whom 4 had OH. In conclusion, although OH commonly occurs in our institutionalized elderly patients, their association with diseases or medications that typically affect postural circulatory adjustment did not reach statistical significance. The condition of frail elderly could itself be a sufficient cause of OH